The Hidden Cost of Academic Excellence: Academic Burnout among Moroccan CPGE Students - Ouhejjou, Mohamed (International Journal of Language and Literary Studies, 2024)
Student burnout has emerged as a salient concern in high-stakes academic environments worldwide; yet its manifestation within Morocco’s Classes Préparatoires aux Grandes Écoles (CPGE) remains conspicuously underexplored. Characterised by an exceptionally demanding curriculum, relentless competitive pressure, and a cultural milieu that invests considerable social prestige in academic attainment, the CPGE system constitutes a particularly fertile ground for the chronic academic stress that precipitates burnout. The present study examined the prevalence and dimensional structure of burnout among 101 Moroccan CPGE students (58 female, 43 male) through an adapted version of the Maslach Burnout Inventory–Student Survey (MBI-SS; Schaufeli et al., 2002), applying Maslach and Leiter’s (1997) tripartite model of exhaustion, cynicism, and reduced academic efficacy. The findings attest to alarmingly elevated exhaustion (subscale M = 4.03/5), moderate but pervasive cynicism (M = 3.48), and a bifurcated efficacy picture in which residual goal-motivation coexists with markedly attenuated classroom confidence (M = 3.60). Taken together, these results position this population within an intermediate stage of burnout whose trajectory is unlikely to self-correct without deliberate intervention at the classroom, institutional, and policy levels. Future longitudinal and gender-comparative research is recommended to build a more robust empirical foundation for evidence-based well-being initiatives within Morocco’s elite preparatory sector.